Booktubers: performances e conversações em torno do livro e da leitura na comunidade booktube - Jeffman, Tauana Mariana Weinberg (Universidade do Vale do Rio dos Sinos, 2017)
The following dissertation was guided by the principle of the scientific investigation and by the efforts to understand relations established between readers of the booktube community and readings from the taste performance of booktubers in their own channels on YouTube. I do contextualize few aspects of book history and reading history and intend to provide a problematization of their transformations under the advent of social networks. These discussions are based on the concepts of Reading, Consumption, Tasting performance, Cultural Materialism, Social Networks and Virtual Communities. The empirical research was developed under an ethnographic perspective, and it has the virtual environment of YouTube as a field, as a field, in order to approach the phenomenon through a systematic vigilant activity. The scientific observation of booktubers activities and their audiovisual productions (at least of them were fuly analyzed considering conversations, comments and repercussions). When it comes to concepts, I built analsys of the performance of tasting and the representations of the self performed by the booktubers. Their relations, conversations, negotiations and conflicts undertaken within the community were also themes of interest in this work. Considering how the culture of internet works, I assume that in booktube community the reader is a network reader who plays on a platform determinated essentially by the culture of social interaction, and it acts in the making of it, building a whole community establishing relationships through the multiples ways that the book and the reading habbit are enjoyed.
Keywords: Comunidade; Leitores; Livros; YouTube; Community; Readers; Books; Booktubers; ACCNPQ::Ciências Sociais Aplicadas::Comunicação